Europe's quiet administrative governance of migrant integration - Wersig, J (2019)
Amidst the so-called refugee and migration crisis, the ‘European Integration Network’ (EIN) was established in 2016 as a European Union soft-governance practice. The thesis analyses how administrators learn in soft-governance networks, studying in particular what mechanisms are involved in facilitating different types of learning and conditions under which they operate best. Studies on micro-level roots and mechanisms of learning are surprisingly scarce. Relying on 50+ interviews with EIN practitioners and documents, this thesis finds that facilitated networking and ‘soft’ interactions result in updating individual administrators’ beliefs regarding policy instruments (‘instrumental learning’) and their paradigmatic frames (‘paradigmatic learning’). This is triggered, amplified, and sustained by transformational conduits. Professional trust within peer groups determines which instruments administrators choose. Meanwhile, informal, emotionally-charged interactions with stakeholders frame instruments. Updated frames may in turn penetrate a trusted peer group with a specific instrumental focus. Alongside the organic interaction of conduits, their purposive activation in two ideal-type practices is explored: (i) platforming, recurrent interactions within a formal network structure, and (ii) elevating, accelerated experiences within network sub-groups. The European Commission asserts itself in learning by managing the net-work and encouraging members with aligned paradigms and organisational resources to co-shape these practices. In particular elevating activates conduits that establish direct paradigmatic experiences resonating in subsequent networking. Findings are probed by exploring learning about Portuguese migrant one-stop-shops and Swedish collaborative governance. The probes underscore a social dimension of learning. Ties created at the elevating stage iterate back to the platform and compound network effects as peer groups re-shuffle and gateways open. Overall, the focus on administrative learning contributes to better understanding how soft governance operates quietly under the political or legalistic surface. Under the right conditions, exchange on policy instruments and frames about migrant integration appear more successful than posited by other studies.